Does the learner profiler successfully screen for neurodiversity and predict neuropsychological outcomes in high school learners? - Antvorskov, Khayreyah (Department of Psychology, 2024)
There has been a push for improved inclusive education for learners with learning difficulties and disabilities in SA due to the long-lasting detrimental consequences learning difficulties and disabilities have on learners' academic achievement and future outcomes. The importance of the screening and identification of learning difficulties and disabilities has been highlighted as the current screening policy in SA presents several issues and formal neuropsychological tests are time-consuming, costly, require expertise in administration, and lack language diversity. Therefore, computerized assessments, such as the Learner Profiler, have been put forward as a useful supportive tool to aid the screening for, and identification of, learning difficulties and disabilities. The current study investigated if the Learner Profiler, a computerized assessment tool, could successfully predict working memory, numeracy and literacy outcomes from formal neuropsychological pen and paper tests in a sample of high school learners. Participants were recruited from English-medium Cape Town high schools (N= 51). Participants first completed the Learner Profiler working memory, literacy and numeracy modules (stage 1) and then were later administered the KTEA-3 and the Working Memory Index from the WISC-IV (stage 2). It was found that the working memory outcomes from the Learner Profiler significantly predicted the overall Working Memory Index outcomes (p < .001) but not outcomes from the Digit Span Backwards and Letter-number Sequencing individual subtests (p > .05). The numeracy outcomes from the Learner Profiler did not significantly predict the outcomes from the numeracy neuropsychological pen and paper tests (p > .05). However, excluding one reading subtest (p >.05), the literacy outcomes from the Learner Profiler significantly predicted the literacy outcomes from the KTEA-3 (p